Is there any relationship between match running, technical-tactical performance, and team success in professional soccer? A longitudinal study in the first and second divisions of LaLiga - Oliva-Lozano, J. M.; Martínez-Puertas, H.; Fortes, V.; Campo, R. L.; Resta, R.; Muyor, J. M. (Biology of Sport, 2023)
The aim of this study was to analyze the association between teams` success at the end of the season and match running, and technical-tactical performance in two professional soccer leagues. Match running, and technical-tactical performance data were collected during two consecutive seasons. A Factor Analysis was conducted to reduce the number of performance variables into a fewer number of factors. The scree plot with parallel analysis revealed that five factors should be retained. Then, a multiple linear regression analysis was performed to explain which variables and factors were more associated with teams` success at the end of the season. The main findings of this study were that factor 3, which was correlated with goals scored, possessions ending with a goal, shots on target, goals from set plays, goals from a direct free kick, offsides, and goals conceded, was the most important contributor to teams` success (ß = 0.66). In addition, this study observed a significant interaction (p = 0.001) between the second division of LaLiga and factor 2, which correlated with total distance (TD), sprinting distance (SPD), and sprinting actions (SPA) when opponent team owns the ball, tackles, shots inside the box, and fouls received. This implies that factor 2 had a different effect on the total points at the end of the season depending on the league. However, factor 2 had no effect on the first division. In conclusion, technical-tactical performance variables were usually more closely linked to the team`s success in both leagues than match running performance data. Regarding the technical-tactical performance, teams may focus on drills that promote goal situations, shooting accuracy, the total of shots performed in match play, and set pieces. However, defensive skills need to be reinforced considering the importance of goals conceded for team success in both divisions. When it comes to the match running performance, teams are encouraged to focus on offensive actions, in which they possess and run with the ball (especially at high speed) and defensive actions in which the players perform continuous and high-intensity physical efforts to prevent the opponents from scoring, avoid counterattacks, stay compact, and defend the area and goal.